1973
DOI: 10.3758/bf03198115
|View full text |Cite
|
Sign up to set email alerts
|

The concreteness of attributes in concept learning strategies

Abstract: Ss were presented with conjunctive concept learning tasks using geometric stimuli in two experiments and using combinations of abstract characteristics in two other experiments. Evidence indicated that the conjunctive hypotheses for geometric stimuli were not mediated by component values but were sampled as unitized wholes. In contrast, conjunctive hypotheses for abstract attributes were sampled via independent combinations of component values. The differential processing was not found to be associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Shepp and Barrett (1991) found that children are better able to acquire a conjunctive categorization when the conjoined dimensions are connected in the same object than when they are physically separated. Nahinsky, Slaymaker, Aamiry, and O'Brien (1973) similarly found that physical proximity of stimulus parts facilitated acquiring concepts that involved several of the parts. Finally, Saiki and Hummel (1996) found that concepts based on the conjunction of the shape of an object and its spatial location relative to a second object were much more easily acquired when the two objects were physically connected than when they were separated.…”
Section: Methodsmentioning
confidence: 86%
“…Shepp and Barrett (1991) found that children are better able to acquire a conjunctive categorization when the conjoined dimensions are connected in the same object than when they are physically separated. Nahinsky, Slaymaker, Aamiry, and O'Brien (1973) similarly found that physical proximity of stimulus parts facilitated acquiring concepts that involved several of the parts. Finally, Saiki and Hummel (1996) found that concepts based on the conjunction of the shape of an object and its spatial location relative to a second object were much more easily acquired when the two objects were physically connected than when they were separated.…”
Section: Methodsmentioning
confidence: 86%
“…It is possible then that the positive effects observed here are due, in part, to instance imagery, a variable previously shown to influence ease of concept identification (Katz & Denny, 1977;Katz & Paivio, 1975;Reed & Dick, 1968). Since the present findings cannot be attributed to the controlled variable of image saliency dominance, an imagery based argument for these results would have to assume some other aspect of the imagery system, such as prevalence of parallel processing, is responsible for the increased availability of sensory information (see Nahinsky, Slaymaker, Aamiry, & O'Brien, 1973;Paivio, 1975). In any event, the results are not readily explicable in terms of the traditional interference explanations usually provided for variables analogous to the one manipulated here and further research on the surprising reversal which was observed is clearly warranted.…”
Section: Resultsmentioning
confidence: 64%